Dry-mixed mortar for paving ceramic tiles and preparation method of dry-mixed mortar

By using a combination of silicate cement, quartz sand, water-retaining and tackifying resin and modified thickener in dry powder mortar, the problem of poor water-retaining performance of dry powder mortar is solved, and the construction performance and service life in tiles are improved.

CN119306460APending Publication Date: 2025-01-14SUZHOU GANGSONG BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411431955.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The dry powder mortar has poor water retention performance in tiles paving, resulting in water loss, cracking and short service life, affecting construction performance and stability.

Method used

Using a combination of silicate cement, quartz sand, water-retaining and tackifying resin, composite capacity-enhancing modified filler and modified thickener, the water-retaining and adhesion properties of dry powder mortar are improved through cross-linking reaction and compound modification treatment. and stability.

Benefits of technology

It significantly improves the water retention rate, freezing resistance and compressive strength of dry powder mortar, extends the service life, and enhances construction performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005083903880000091
    Figure BDA0005083903880000091
  • Figure BDA0005083903880000101
    Figure BDA0005083903880000101
Patent Text Reader

Abstract

The invention relates to dry-mixed mortar for paving ceramic tiles and a preparation method thereof, and relates to the technical field of building materials, and the dry-mixed mortar comprises the following components in parts by mass: 60-80 parts of Portland cement, 30-40 parts of quartz sand, 30-40 parts of water-retention tackifying resin, 20-30 parts of a composite compatibilization modified filler, 10-15 parts of lime putty, and 5-10 parts of a modified thickener. The effect of improving the water retention performance of the dry-mixed mortar is achieved, and the dry-mixed mortar has high bonding strength, compressive strength and good anti-freezing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to a dry mortar for tile paving and a preparation method thereof. Background Art

[0002] Dry mortar, also known as dry-mixed mortar, is a commonly used building material. Dry mortar is obtained by uniformly mixing cement, sand, mineral admixtures and functional additives in a certain proportion in a dry state. It is a mixture in a granular or powdered state. The state's support for the dry mortar industry has led to the widespread use of dry mortar. In the construction and decoration of residential buildings, the paving process of floor tiles has gradually shifted from the construction mode of mixing and preparing ordinary cement mortar on site to the use of dry mortar.

[0003] With the large-scale use in floor tile paving, dry-mix mortar has also exposed certain shortcomings. The water retention performance of dry-mix mortar is poor, because the powder material structure of dry-mix mortar is relatively loose and permeable, and water can easily penetrate through its surface, which is easy to lose water, thus affecting the bonding performance and making the dry-mix mortar prone to cracking during the curing process. The water retention performance affects the construction performance and service life of dry-mix mortar, so it needs to be improved. Summary of the invention

[0004] In order to improve the water retention performance of dry-mix mortar, the present application provides a dry-mix mortar for tile paving and a preparation method thereof.

[0005] The present application provides a dry mortar for tile paving and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a dry mortar for tile paving, which adopts the following technical solution: A dry mortar for tile paving, comprising the following components in parts by weight: 60-80 parts of Portland cement 30-40 parts of quartz sand 30-40 parts of water-retaining and tackifying resin 20-30 parts of composite volume-enhancing modified filler 10-15 parts of lime paste Modified thickener 5-10 parts.

[0006] The dry-mix mortar prepared by silicate cement, quartz sand, water-retaining tackifying resin, composite volume-increasing modified filler, lime paste and modified thickener has good water-retaining performance. The water-retaining tackifying resin improves the water-retaining and adhesion properties of the dry-mix mortar. The composite volume-increasing modified filler improves the dispersibility of the filler and the compatibility of the system through the compounding and modification of a variety of fillers, and can play a good reinforcement and toughening effect on the dry-mix mortar, thereby improving the stability. The modified thickener can improve the water retention rate of the dry-mix mortar, alleviate the hydration effect during the water loss process, and improve the stability and service life of the dry-mix mortar.

[0007] Preferably, the water-retaining tackifying resin comprises enolate grafted acrylate, lignin-based polyol and hydroxymethyl urea.

[0008] Enol grafted acrylate can be cross-linked with hydroxymethyl urea to form a semi-interpenetrating network structure. Enol grafted acrylate has acrylate groups and enol groups, and has good water retention, adhesion and weather resistance. Through cross-linking polymerization with hydroxymethyl urea, the adhesion and stability of the water-retaining tackifying resin can be further improved; lignin-based polyols have rich hydroxyl structures, can retain moisture, and have good cold resistance under low temperature conditions. They can synergistically improve the water retention, adhesion and antifreeze properties of the water-retaining tackifying resin with enol grafted acrylate and hydroxymethyl urea.

[0009] Preferably, the mass ratio of the enol grafted acrylate, the lignin-based polyol and the hydroxymethyl urea is 1:(0.14-0.22):0.16.

[0010] The water-retaining tackifying resin prepared according to the above mass ratio has good water-retaining performance, adhesion performance and antifreeze performance.

[0011] Preferably, the enol grafted acrylate comprises cyclopentenol, acrylic acid and N-vinyl acrylamide.

[0012] The cyclopentenol group can improve the weather resistance of acrylate and the antifreeze performance of enol grafted acrylate; N-vinyl acrylamide can improve the reactivity and weather resistance of enol grafted acrylate, so that the enol grafted acrylate can better undergo interpenetrating cross-linking reaction with hydroxymethyl urea, thereby improving the adhesion, water retention and antifreeze performance of the water-retaining tackifying resin.

[0013] Preferably, the raw materials for preparing the composite volume-extending and modified filler include composite filler, silicone and polyethylene glycol.

[0014] The composite filler has good water retention and antifreeze properties. Through the compound modification treatment of silicone and polyethylene glycol, the number of active groups on the surface of the composite filler is increased, the dispersibility, compatibility and adhesion properties of the composite volume-enhanced modified filler are improved, and the overall stability of the dry-mix mortar is improved, thereby improving the water retention, antifreeze and adhesion properties of the dry-mix mortar.

[0015] Preferably, the composite filler comprises mica, expanded perlite and cellulose fiber.

[0016] Mica, expanded perlite and cellulose fiber have rich pore structures and adsorption properties, can store water molecules and air, and have good water retention and antifreeze properties; the composite filler reinforces and toughens the dry-mix mortar through the synergistic effect of the compound of mica, expanded perlite and cellulose fiber, thereby improving the stability and compressive strength of the dry-mix mortar.

[0017] Preferably, the mass ratio of the composite filler, silicone and polyethylene glycol is 1:(0.15-0.27):0.4.

[0018] The dry-mix mortar prepared according to the above mass ratio has good water retention, frost resistance, adhesion and compressive strength.

[0019] Preferably, the raw materials for preparing the modified thickener include cetyltrimethylammonium bromide, lauroyl chloride and xanthan gum.

[0020] Xanthan gum is modified by hexadecyltrimethylammonium bromide and lauroyl chloride, and quaternary ammonium salts and acyl chlorides are introduced into the xanthan gum molecules, which can improve the solubility and dispersibility of xanthan gum, increase the structural stability of xanthan gum molecules, and improve the adhesion and tack properties of xanthan gum, so that the modified thickener has better thickening effect, strong adhesion and gelling properties.

[0021] Preferably, the mass ratio of hexadecyltrimethylammonium bromide, lauroyl chloride and xanthan gum is (0.18-0.36):0.2:1.

[0022] The modified thickener prepared according to the above mass ratio has good adhesion and antifreeze properties.

[0023] In a second aspect, the present application provides a method for preparing dry mortar for tile paving, which adopts the following technical solution: A method for preparing dry mortar for tile paving, comprising the following preparation steps: The silicate cement, quartz sand, water-retaining tackifying resin, composite volume-increasing modified filler, lime paste and modified thickener are mixed and stirred, and the materials are discharged to obtain dry mortar for tile paving.

[0024] The dry mortar for tile paving prepared according to the above steps has good water retention, adhesion, frost resistance and compressive strength.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. The dry-mix mortar prepared by silicate cement, quartz sand, water-retaining tackifying resin, composite volume-increasing modified filler, lime paste and modified thickener has good water-retaining performance. The water-retaining tackifying resin improves the water-retaining and adhesion properties of the dry-mix mortar; the composite volume-increasing modified filler improves the dispersibility of the filler and the compatibility of the system through the compounding and modification of a variety of fillers, and can play a good reinforcement and toughening effect on the dry-mix mortar, thereby improving the stability; the modified thickener can improve the water retention rate of the dry-mix mortar, alleviate the hydration effect during the water loss process, and improve the stability and service life of the dry-mix mortar.

[0026] 2. Enol grafted acrylate can be cross-linked with hydroxymethyl urea to form a semi-interpenetrating network structure. Enol grafted acrylate has acrylate groups and enol groups, and has good water retention, adhesion and weather resistance. Through cross-linking polymerization with hydroxymethyl urea, the adhesion and stability of the water-retaining tackifying resin can be further improved; lignin-based polyols have rich hydroxyl structures, can retain moisture, and have good cold resistance under low temperature conditions. They can synergistically improve the water retention, adhesion and antifreeze properties of the water-retaining tackifying resin with enol grafted acrylate and hydroxymethyl urea.

[0027] 3. The composite filler has good water retention and antifreeze properties. Through the compound modification treatment of silicone and polyethylene glycol, the number of active groups on the surface of the composite filler is increased, the dispersibility, compatibility and adhesion properties of the composite volume-enhanced modified filler are improved, and the overall stability of the dry-mix mortar is improved, thereby improving the water retention, antifreeze and adhesion properties of the dry-mix mortar.

[0028] 4. Xanthan gum is modified by hexadecyltrimethylammonium bromide and lauroyl chloride, and quaternary ammonium salts and acyl chlorides are introduced into the xanthan gum molecules, which can improve the solubility and dispersibility of xanthan gum, increase the structural stability of xanthan gum molecules, and improve the adhesion and tackiness of xanthan gum, so that the modified thickener has better thickening effect, strong adhesion and gelling properties. DETAILED DESCRIPTION

[0029] The present application discloses a dry mortar for tile paving and a preparation method thereof. The present application is further described in detail below in conjunction with the embodiments: Example 1 Preparation of water-retaining and tackifying resin 35 kg of potassium hydroxide was dispersed in 35 L of deionized water to obtain a potassium hydroxide aqueous solution, 50 kg of acrylic acid was added to the potassium hydroxide aqueous solution to obtain a neutralized acrylic acid solution, 25 kg of methylcyclopentenolone (CAS No.: 80-71-7) was dissolved in 200 L of deionized water under 90° C. water bath conditions to obtain a methylcyclopentenolone aqueous solution. The neutralized acrylic acid solution and 1 kg of N-vinyl acrylamide (CAS No.: 2956-58-3) were added to the methylcyclopentenolone aqueous solution, 0.1 kg of potassium persulfate was added under ice bath conditions, nitrogen was passed through for 5 minutes, the reactor was placed in a 55° C. water bath, stirred at a speed of 200 rpm for 4 hours to obtain a product, the product was dried in a 60° C. oven, the dried product was crushed, the crushed product was washed with ethanol and then placed in a 60° C. oven for drying again to obtain enol grafted acrylate.

[0030] 1.11 kg of anhydrous glycerol and 2.11 kg of potassium hydroxide are dispersed in 15 L of acetone to obtain a catalyst solution, 12 kg of propylene oxide (CAS No.: 75-56-9), 11.4 kg of lignin (CAS No.: 8068-03-9) and the catalyst solution are mixed and stirred uniformly in a high-pressure reactor, and the mixture is kept at 150° C. for 2 hours with a magnetic stirring speed of 400 rpm to obtain a lignin-based polyol solution, and the lignin-based polyol solution is rotary evaporated to remove the solvent to obtain a lignin-based polyether polyol; 5.38 kg of lignin-based polyol, 6.16 kg of hydroxymethyl urea and 38.46 kg of enol grafted acrylate were mixed and dispersed in 50 L of deionized water to obtain a mixed reaction liquid, 1 kg of potassium persulfate was added to the mixed reaction liquid, and the mixture was stirred and reacted at a speed of 200 rpm for 2 hours to obtain a mixed product, and the mixed product was dried in an oven at 100° C. for 8 hours. The dried mixed product was washed with anhydrous ethanol and then continued to be dried in an oven at 100° C. for 2 hours to obtain a water-retaining tackifying resin.

[0031] Preparation of composite expanded and modified fillers 32.26 kg of composite filler, 4.84 kg of silicone and 12.9 kg of polyethylene glycol (molecular weight of about 2000) were mixed and dispersed in 50 L of anhydrous ethanol to obtain a mixture, the mixture was stirred at 60°C and 500 rpm for 2 hours, a solid was obtained after filtration, and the solid was dried in an oven at 60°C to obtain a composite volume-enhanced modified filler; the mass ratio of mica, expanded perlite and cellulose fiber in the above composite filler was 1:1.5:2, and the above silicone was acryltrimethoxysilane (CAS No.: 2551-83-9).

[0032] Preparation of modified thickener 14.49 kg of xanthan gum was dispersed in 800 L of deionized water, and stirred at 300 rpm in a 40°C water bath until completely dissolved to obtain a xanthan gum solution. 2.61 kg of hexadecyltrimethylammonium bromide (CAS No.: 57-09-0) was added to the xanthan gum solution, and 2.9 kg of lauroyl chloride was added dropwise within 1 hour to obtain a xanthan gum modified liquid. The solution was stirred at 200 rpm in a 80°C water bath for 2 hours, and ethanol was added to the reacted xanthan gum modified liquid for precipitation. The precipitate was washed with anhydrous ethanol, and the washed precipitate was dried in an oven at 40°C to obtain a modified thickener.

[0033] Preparation of dry mortar for tile installation 60 kg of silicate cement, 30 kg of quartz sand, 30 kg of water-retaining tackifying resin, 20 kg of composite volume-increasing modified filler, 10 kg of lime paste and 5 kg of modified thickener were mixed into a mixer, stirred at a speed of 300 rpm for 1 hour, and discharged to obtain dry mortar for tile paving.

[0034] Example 2 Preparation of water-retaining and tackifying resin 35 kg of potassium hydroxide was dispersed in 35 L of deionized water to obtain a potassium hydroxide aqueous solution, 50 kg of acrylic acid was added to the potassium hydroxide aqueous solution to obtain a neutralized acrylic acid solution, 25 kg of methylcyclopentenolone (CAS No.: 80-71-7) was dissolved in 200 L of deionized water under 90° C. water bath conditions to obtain a methylcyclopentenolone aqueous solution. The neutralized acrylic acid solution and 1 kg of N-vinyl acrylamide (CAS No.: 2956-58-3) were added to the methylcyclopentenolone aqueous solution, 0.1 kg of potassium persulfate was added under ice bath conditions, nitrogen was passed through for 5 minutes, the reactor was placed in a 55° C. water bath, stirred at a speed of 200 rpm for 4 hours to obtain a product, the product was dried in a 60° C. oven, the dried product was crushed, the crushed product was washed with ethanol and then placed in a 60° C. oven for drying again to obtain enol grafted acrylate.

[0035] 1.11 kg of anhydrous glycerol and 2.11 kg of potassium hydroxide are dispersed in 15 L of acetone to obtain a catalyst solution, 12 kg of propylene oxide (CAS No.: 75-56-9), 11.4 kg of lignin (CAS No.: 8068-03-9) and the catalyst solution are mixed and stirred uniformly in a high-pressure reactor, and the mixture is kept at 150° C. for 2 hours with a magnetic stirring speed of 400 rpm to obtain a lignin-based polyol solution, and the lignin-based polyol solution is rotary evaporated to remove the solvent to obtain a lignin-based polyether polyol; 7.97 kg of lignin-based polyol, 5.8 kg of hydroxymethyl urea and 36.23 kg of enol grafted acrylate were mixed and dispersed in 50 L of deionized water to obtain a mixed reaction liquid, 1 kg of potassium persulfate was added to the mixed reaction liquid, and the mixture was stirred at a speed of 200 rpm for 2 hours to obtain a mixed product, and the mixed product was dried in an oven at 100° C. for 8 hours. The dried mixed product was washed with anhydrous ethanol and then continued to be dried in an oven at 100° C. for 2 hours to obtain a water-retaining tackifying resin.

[0036] Preparation of composite expanded and modified fillers 29.94 kg of composite filler, 8.08 kg of silicone and 11.98 kg of polyethylene glycol (molecular weight of about 2000) were mixed and dispersed in 50 L of anhydrous ethanol to obtain a mixture, the mixture was stirred at 60° C. and 500 rpm for 2 hours, a solid was obtained after filtration, and the solid was dried in an oven at 60° C. to obtain a composite volume-enhanced modified filler; the mass ratio of mica, expanded perlite and cellulose fiber in the above composite filler was 1:1.5:2, and the above silicone was acryltrimethoxysilane (CAS No.: 2551-83-9).

[0037] Preparation of modified thickener 12.82 kg of xanthan gum was dispersed in 800 L of deionized water, and stirred at 300 rpm in a 40°C water bath until completely dissolved to obtain a xanthan gum solution. 4.62 kg of hexadecyltrimethylammonium bromide (CAS No.: 57-09-0) was added to the xanthan gum solution, and 2.56 kg of lauroyl chloride was added dropwise within 1 hour to obtain a xanthan gum modified liquid. The solution was stirred at 200 rpm in a 80°C water bath for 2 hours, and ethanol was added to the reacted xanthan gum modified liquid for precipitation. The precipitate was washed with anhydrous ethanol, and the washed precipitate was dried in an oven at 40°C to obtain a modified thickener.

[0038] Preparation of dry mortar for tile installation 80 kg of silicate cement, 40 kg of quartz sand, 40 kg of water-retaining tackifying resin, 30 kg of composite volume-increasing modified filler, 15 kg of lime paste and 10 kg of modified thickener were mixed into a mixer, stirred at a speed of 300 rpm for 1 hour, and discharged to obtain dry mortar for tile paving.

[0039] Example 3 Preparation of water-retaining and tackifying resin 35 kg of potassium hydroxide was dispersed in 35 L of deionized water to obtain a potassium hydroxide aqueous solution, 50 kg of acrylic acid was added to the potassium hydroxide aqueous solution to obtain a neutralized acrylic acid solution, 25 kg of methylcyclopentenolone (CAS No.: 80-71-7) was dissolved in 200 L of deionized water under 90° C. water bath conditions to obtain a methylcyclopentenolone aqueous solution. The neutralized acrylic acid solution and 1 kg of N-vinyl acrylamide (CAS No.: 2956-58-3) were added to the methylcyclopentenolone aqueous solution, 0.1 kg of potassium persulfate was added under ice bath conditions, nitrogen was passed through for 5 minutes, the reactor was placed in a 55° C. water bath, stirred at a speed of 200 rpm for 4 hours to obtain a product, the product was dried in a 60° C. oven, the dried product was crushed, the crushed product was washed with ethanol and then placed in a 60° C. oven for drying again to obtain enol grafted acrylate.

[0040] 1.11 kg of anhydrous glycerol and 2.11 kg of potassium hydroxide are dispersed in 15 L of acetone to obtain a catalyst solution, 12 kg of propylene oxide (CAS No.: 75-56-9), 11.4 kg of lignin (CAS No.: 8068-03-9) and the catalyst solution are mixed and stirred uniformly in a high-pressure reactor, and the mixture is kept at 150° C. for 2 hours with a magnetic stirring speed of 400 rpm to obtain a lignin-based polyol solution, and the lignin-based polyol solution is rotary evaporated to remove the solvent to obtain a lignin-based polyether polyol; 6.72 kg of lignin-based polyol, 5.97 kg of hydroxymethyl urea and 37.31 kg of enol grafted acrylate were mixed and dispersed in 50 L of deionized water to obtain a mixed reaction liquid, 1 kg of potassium persulfate was added to the mixed reaction liquid, and the mixture was stirred and reacted at a speed of 200 rpm for 2 hours to obtain a mixed product, and the mixed product was dried in an oven at 100° C. for 8 hours. The dried mixed product was washed with anhydrous ethanol and then continued to be dried in an oven at 100° C. for 2 hours to obtain a water-retaining tackifying resin.

[0041] Preparation of composite expanded and modified fillers 31.06 kg of composite filler, 6.52 kg of silicone and 12.42 kg of polyethylene glycol (molecular weight of about 2000) were mixed and dispersed in 50 L of anhydrous ethanol to obtain a mixture, the mixture was stirred at 60°C and 500 rpm for 2 hours, a solid was obtained after filtration, and the solid was dried in an oven at 60°C to obtain a composite volume-enhanced modified filler; the mass ratio of mica, expanded perlite and cellulose fiber in the above composite filler was 1:1.5:2, and the above silicone was acryltrimethoxysilane (CAS No.: 2551-83-9).

[0042] Preparation of modified thickener 13.61 kg of xanthan gum was dispersed in 800 L of deionized water, and stirred at 300 rpm in a 40°C water bath until completely dissolved to obtain a xanthan gum solution. 3.67 kg of hexadecyltrimethylammonium bromide (CAS No.: 57-09-0) was added to the xanthan gum solution, and 2.72 kg of lauroyl chloride was added dropwise within 1 hour to obtain a xanthan gum modified liquid. The solution was stirred at 200 rpm in a 80°C water bath for 2 hours, and ethanol was added to the reacted xanthan gum modified liquid for precipitation. The precipitate was washed with anhydrous ethanol, and the washed precipitate was dried in an oven at 40°C to obtain a modified thickener.

[0043] Preparation of dry mortar for tile installation 70 kg of silicate cement, 35 kg of quartz sand, 35 kg of water-retaining tackifying resin, 25 kg of composite volume-increasing modified filler, 12.5 kg of lime paste and 7.5 kg of modified thickener were mixed into a mixer, stirred at a speed of 300 rpm for 1 hour, and discharged to obtain dry mortar for tile paving.

[0044] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of enol grafted acrylate is 40.32 kg, the amount of lignin-based polyol is 3.23 kg, and the amount of hydroxymethyl urea is 6.45 kg.

[0045] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of enol grafted acrylate is 34.24 kg, the amount of lignin-based polyol is 10.28 kg, and the amount of hydroxymethyl urea is 5.48 kg.

[0046] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the amount of composite filler used is 33.78 kg, the amount of silicone used is 2.7 kg, and the amount of polyethylene glycol used is 13.52 kg.

[0047] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of composite filler used is 27.78 kg, the amount of silicone used is 11.11 kg, and the amount of polyethylene glycol used is 11.11 kg.

[0048] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of hexadecyltrimethylammonium bromide used is 1.54 kg, the amount of lauroyl chloride used is 3.08 kg, and the amount of xanthan gum used is 15.38 kg.

[0049] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the amount of hexadecyltrimethylammonium bromide used is 5.89 kg, the amount of lauroyl chloride used is 2.35 kg, and the amount of xanthan gum used is 11.76 kg.

[0050] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the enol-grafted acrylate in the step of preparing the water-retaining tackifying resin is replaced by acrylate.

[0051] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, no lignin-based polyol is added in the step of preparing the water-retaining tackifying resin.

[0052] Example 12 Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, no hydroxymethyl urea is added in the step of preparing the water-retaining tackifying resin.

[0053] Example 13 Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that in Example 13, no silicone is added in the step of preparing the composite volume-extending and modified filler.

[0054] Embodiment 14 Example 14 is based on Example 3. The only difference between Example 14 and Example 3 is that in Example 14, polyethylene glycol is not added in the step of preparing the composite expanded modified filler.

[0055] Embodiment 15 Example 15 is based on Example 3. The only difference between Example 15 and Example 3 is that in Example 15, the composite filler in the step of preparing the composite volume-extending and modified filler is replaced by mica.

[0056] Example 16 Example 16 is based on Example 3. The only difference between Example 16 and Example 3 is that in Example 16, no hexadecyltrimethylammonium bromide is added in the step of preparing the modified thickener.

[0057] Embodiment 17 Example 17 is based on Example 3. The only difference between Example 17 and Example 3 is that in Example 17, no lauroyl chloride is added in the step of preparing the modified thickener.

[0058] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the water-retaining tackifying resin is replaced by a redispersible latex powder.

[0059] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the composite volume-increasing and modified filler is replaced by mica.

[0060] Comparative Example 3 Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, the modified thickener is replaced by xanthan gum.

[0061] Performance testing (1) Select "DIN18557-7 Test Method for Inorganic Cementitious Mortar" as the standard, weigh and record the mass of dry mortar and the mass of mortar after water absorption, and divide the added water mass by the dry weight of mortar to obtain the water retention rate. Each sample is tested three times, and the average value is taken after measurement. The results are recorded in Table 1.

[0062] (2) GB / T29756-2013 Test method for physical properties of dry-mixed mortar and GB / T20473-2021 Building thermal insulation mortar were selected as the standards. The mortar mixed with water was prepared into a 40mm*40m*160mm prismatic specimen, and the 28d compressive strength of the specimen was tested. The specimens prepared above were subjected to freeze-thaw cycle curing for 28d, and the compressive strength after freeze-thaw cycle was tested, and the strength loss rate was calculated. The mortar mixed with water was applied to the surface of the substrate, and after the mortar hardened, the pull-out joint was glued to the surface, and a certain stress was applied until it was destroyed. The ratio of the destructive force value to the test area was the tensile bond strength. Three samples were prepared for each sample, and the average value was taken after measurement. The results are recorded in Table 1.

[0063] Table 1 Test results of water retention, compressive strength, frost resistance and adhesion performance of dry mortar It can be seen from Table 1 that the water retention rate of Examples 1-3 is greater than 95.4%, the compressive strength is greater than 56.1 MPa, the strength loss rate is less than 4.2%, and the bonding strength is greater than 1.16 MPa. It can be seen that the dry mortar prepared in the present application has good water retention, compressive strength, frost resistance and adhesion properties.

[0064] As shown in Table 1, the difference between Examples 4 and 5 and Example 3 is that the mass ratio of enol grafted acrylate, lignin-based polyol and hydroxymethyl urea in Example 4 is 1:0.08:0.16, and the mass ratio of enol grafted acrylate, lignin-based polyol and hydroxymethyl urea in Example 5 is 1:0.3:0.16. The water retention rate in Examples 4 and 5 is less than 95.1%, the compressive strength is less than 55.9 MPa, the strength loss rate is greater than 4.3%, and the bonding strength is less than 1.13 MPa. The water retention rate in Example 3 is 96.5%, the compressive strength is less than 55.9 MPa, the strength loss rate is greater than 4.3%, and the bonding strength is less than 1.13 MPa. The hardness is 57.2MPa, the strength loss rate is 3.5%, and the bonding strength is 1.29MPa. Compared with Example 3, the water retention performance, compressive strength, frost resistance and adhesion performance of Examples 4 and 5 are all reduced; this is because the mass ratio of enol grafted acrylate, lignin-based polyol and hydroxymethyl urea is not within the specified range. Too much or too little lignin-based polyol will affect the stability and reaction performance of the water-retaining tackifying resin, and then affect the dispersibility and compatibility of the dry-mixed mortar. Therefore, the water retention performance, compressive strength, frost resistance and adhesion performance are all reduced.

[0065] As can be seen from Table 1, the only difference between Examples 6 and 7 and Example 3 is that the mass ratio of the composite filler, silicone and polyethylene glycol in Example 6 is 1:0.08:0.4, and the mass ratio of the composite filler, silicone and polyethylene glycol in Example 7 is 1:0.4:0.4. The water retention rate in Examples 6 and 7 is less than 94.6%, the compressive strength is less than 53.8 MPa, the strength loss rate is greater than 4.5%, and the bonding strength is less than 1.06 MPa. Compared with Example 3, Examples 6 and 7 have reduced water retention, compressive strength, antifreeze performance and adhesion performance; this is because the mass ratio of the composite filler, silicone and polyethylene glycol is not within the specified range, and too much or too little silicone will affect the dispersibility, compatibility and adhesion performance of the composite volume-enhancing modified filler, thereby affecting the stability of the dry-mixed mortar, so the water retention, compressive strength, antifreeze performance and adhesion performance are all reduced.

[0066] As can be seen from Table 1, the only difference between Examples 8 and 9 and Example 3 is that the mass ratio of hexadecyltrimethylammonium bromide, lauroyl chloride and xanthan gum in Example 8 is 0.1:0.2:1, and the mass ratio of hexadecyltrimethylammonium bromide, lauroyl chloride and xanthan gum in Example 9 is 0.5:0.2:1. The water retention rate in Examples 8 and 9 is less than 94.6%, the compressive strength is less than 52.8MPa, the strength loss rate is greater than 4.9%, and the bonding strength is less than 1.01MPa. Compared with Example 3, Examples 8 and 9 have reduced water retention, compressive strength, antifreeze performance and adhesion performance; this is because the mass ratio of hexadecyltrimethylammonium bromide, lauroyl chloride and xanthan gum is not within the specified range, too much or too little quaternary ammonium salt will affect the dispersibility of the modified thickener and the intercalation thickening performance, and the performance degradation of the thickener will reduce the overall stability of the dry mortar system, so the water retention, compressive strength, antifreeze performance and adhesion performance are all reduced.

[0067] As can be seen from Table 1, the only difference between Examples 10, 11, and 12 and Example 3 is that in Example 10, the enol grafted acrylate in the step of preparing the water-retaining tackifying resin is replaced with acrylate, in Example 11, the step of preparing the water-retaining tackifying resin does not add lignin-based polyol, and in Example 12, the step of preparing the water-retaining tackifying resin does not add hydroxymethyl urea. In Examples 10, 11, and 12, the water retention rate is less than 92.1%, the compressive strength is less than 50.5 MPa, the strength loss rate is greater than 6.1%, and the bonding strength is less than 0.88 M Pa, compared with Example 3, Examples 10, 11, and 12 have reduced water retention, compressive strength, antifreeze and adhesion properties; this is because the synthetic components of the water-retaining tackifying resin are replaced, the introduction of enol groups is lacking, the weather resistance and antifreeze properties are reduced, and the lack of lignin-based polyols or hydroxymethyl urea reduces the number of active groups of the water-retaining tackifying resin, and the reactivity and compatibility are reduced. All three will affect the stability of the water-retaining tackifying resin, so the water retention, compressive strength, antifreeze and adhesion properties are reduced.

[0068] As shown in Table 1, the only difference between Examples 13, 14, and 15 and Example 3 is that: in Example 13, the step of preparing the composite volume-increasing and modified filler does not add silicone, in Example 14, the step of preparing the composite volume-increasing and modified filler does not add polyethylene glycol, and in Example 15, the composite filler in the step of preparing the composite volume-increasing and modified filler is replaced with mica. In Examples 13, 14, and 15, the water retention rate is less than 93.2%, the compressive strength is less than 51.7 MPa, the strength loss rate is greater than 5.2%, and the bonding strength is less than 1.00 MPa. In Examples 13, 14, and 15, the water retention rate is less than 93.2%, the compressive strength is less than 51.7 MPa, the strength loss rate is greater than 5.2%, and the bonding strength is less than 1.00 MPa. , 15 and Example 3, the water retention, compressive strength, frost resistance and adhesion properties are all reduced; this is because without adding silicone or polyethylene glycol, the number of active groups on the surface of the composite expanded modified filler is reduced, the dispersibility and compatibility in the dry mortar system are reduced, and the composite synergistic effect of the three filler components is lacking. The reinforcement, toughening, water retention and frost resistance of a single mica are limited. All three will reduce the stability and working performance of the composite expanded modified filler, so the water retention, compressive strength, frost resistance and adhesion properties are all reduced.

[0069] As can be seen from Table 1, the only difference between Examples 16 and 17 and Example 3 is that: in Example 16, the step of preparing the modified thickener does not add hexadecyltrimethylammonium bromide, and in Example 17, the step of preparing the modified thickener does not add lauroyl chloride. The water retention rate in Examples 16 and 17 is less than 90.8%, the compressive strength is less than 48.3 MPa, the strength loss rate is greater than 6.9%, and the bonding strength is less than 0.81 MPa. Compared with Example 3, Examples 16 and 17 have reduced water retention, compressive strength, antifreeze and adhesion properties. This is because without adding hexadecyltrimethylammonium bromide or lauroyl chloride, the intercalation adsorption performance of the modified thickener for each component is reduced, the thickening effect is reduced, the adhesion and adhesive properties of the modified thickener are reduced, and the stability of the dry mortar system is reduced, so the water retention, compressive strength, antifreeze and adhesion properties are reduced.

[0070] It can be seen from Table 1 that the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the water-retaining tackifying resin is replaced by a redispersible latex powder, the water retention rate in Comparative Example 1 is 81.8%, the compressive strength is 36.5 MPa, the strength loss rate is 9.2%, and the bonding strength is 0.66 MPa. Compared with Example 3, the water retention performance, compressive strength, antifreeze performance and adhesion performance of Comparative Example 1 are significantly reduced; this is because the water-retaining tackifying resin is replaced by a redispersible latex powder, the dispersed latex powder lacks enol modification, the weather resistance and antifreeze performance are reduced, the cross-linking copolymerization of lignin-based polyols and hydroxymethyl urea is lacking, and a semi-interpenetrating network structure cannot be formed, the water retention performance and adhesion performance are reduced, which further affects the synergistic performance between the components of the dry-mixed mortar, so the water retention performance, compressive strength, antifreeze performance and adhesion performance are significantly reduced.

[0071] It can be seen from Table 1 that the only difference between Comparative Example 2 and Example 3 is that the composite volume-increasing modified filler is replaced with mica in Comparative Example 2, the water retention rate in Comparative Example 2 is 88.3%, the compressive strength is 31.2 MPa, the strength loss rate is 10.5%, and the bonding strength is 0.71 MPa. Compared with Example 3, the water retention performance, compressive strength, antifreeze performance and adhesion performance of Comparative Example 2 are significantly reduced; this is because the composite volume-increasing modified filler is replaced with mica, and the single filler mica lacks a composite synergistic effect, and is not treated with volume-increasing modification of silicone and polyethylene glycol, the active groups on the surface are reduced, and the dispersibility and compatibility in the dry mortar system are reduced, so the water retention performance, compressive strength, antifreeze performance and adhesion performance are significantly reduced.

[0072] As can be seen from Table 1, the difference between Comparative Example 3 and Example 3 is that the modified thickener is replaced by xanthan gum in Comparative Example 3, the water retention rate in Comparative Example 3 is 78.2%, the compressive strength is 33.5 MPa, the strength loss rate is 9.8%, and the bonding strength is 0.61 MPa. Compared with Example 3, the water retention performance, compressive strength, antifreeze performance and adhesion performance of Comparative Example 3 are significantly reduced; this is because the modified thickener is replaced by xanthan gum, and the modification treatment of quaternary ammonium salt and acyl chloride is lacking, the solubility and dispersibility of xanthan gum are reduced, the adhesion performance and gelling performance are reduced, and the structural stability of xanthan gum molecules is reduced, so the water retention performance, compressive strength, antifreeze performance and adhesion performance are significantly reduced.

[0073] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A dry mortar for tile paving, characterized in that: The composition includes the following components in parts by weight: 60-80 parts of Portland cement 30-40 parts of quartz sand 30-40 parts of water-retaining and tackifying resin 20-30 parts of composite volume-enhancing modified filler 10-15 parts of lime paste Modified thickener 5-10 parts.

2. The dry mortar for tile paving according to claim 1, characterized in that: The water-retaining tackifying resin comprises ene alcohol grafted acrylate, lignin-based polyol and hydroxymethyl urea.

3. The dry mortar for tile paving according to claim 2, characterized in that: The mass ratio of the enol grafted acrylate, the lignin-based polyol and the hydroxymethyl urea is 1:(0.14-0.22):0.

16.

4. The dry mortar for tile paving according to claim 3, characterized in that: The enol grafted acrylate comprises cyclopentenol, acrylic acid and N-vinyl acrylamide.

5. The dry mortar for tile paving according to claim 1, characterized in that: The raw materials for preparing the composite volume-increasing and modified filler include composite filler, organic silicon and polyethylene glycol.

6. The dry mortar for tile paving according to claim 5, characterized in that: The composite filler comprises mica, expanded perlite and cellulose fiber.

7. The dry mortar for tile paving according to claim 6, characterized in that: The mass ratio of the composite filler, silicone and polyethylene glycol is 1:(0.15-0.27):0.

4.

8. The dry mortar for tile paving according to claim 1, characterized in that: The raw materials for preparing the modified thickener include hexadecyltrimethylammonium bromide, lauroyl chloride and xanthan gum.

9. The dry mortar for tile paving according to claim 8, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide, lauroyl chloride and xanthan gum is (0.18-0.36):0.2:

1.

10. A method for preparing the dry mortar for tile paving as claimed in claim 1, characterized in that: The method comprises the following preparation steps: The silicate cement, quartz sand, water-retaining tackifying resin, composite volume-increasing modified filler, lime paste and modified thickener are mixed and stirred, and the materials are discharged to obtain dry mortar for tile paving.